2021
DOI: 10.3390/ph14100977
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Bacterial Attachment Mechanisms on Superhydrophobic and Superhydrophilic Substrates

Abstract: Superhydrophilic and superhydrophobic substrates are widely known to inhibit the attachment of a variety of motile and/or nonmotile bacteria. However, the thermodynamics of attachment are complex. Surface energy measurements alone do not address the complexities of colloidal (i.e., bacterial) dispersions but do affirm that polar (acid-base) interactions (ΔGAB) are often more significant than nonpolar (Lifshitz-van der Waals) interactions (ΔGLW). Classical DLVO theory alone also fails to address all colloidal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A unified theory that would explain all aspects of bacterial adhesion still does not exist. Non-specific interactions can be viewed through the thermodynamic approach, classical DLVO (Derjaguin, Landau, Verwey, and Overbeek) theory, or extended DLVO theory, the latter being the most accepted [ 2 , 10 , 11 , 12 ]. In this theory, the bacterial adhesion is described as a balance between attractive long-range Lifshitz–van der Waals forces (i.e., London, dipole-dipole and dipole-induced dipole forces), repulsive or attractive electrostatic forces, and short-range Lewis acid–base (AB) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A unified theory that would explain all aspects of bacterial adhesion still does not exist. Non-specific interactions can be viewed through the thermodynamic approach, classical DLVO (Derjaguin, Landau, Verwey, and Overbeek) theory, or extended DLVO theory, the latter being the most accepted [ 2 , 10 , 11 , 12 ]. In this theory, the bacterial adhesion is described as a balance between attractive long-range Lifshitz–van der Waals forces (i.e., London, dipole-dipole and dipole-induced dipole forces), repulsive or attractive electrostatic forces, and short-range Lewis acid–base (AB) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The cost‐effectiveness of dry sanitation methods has not yet been fully elucidated, which limits large‐scale industrial application. Further studies on the bacteria–substrate interaction on dry surfaces are also essential to allow for the effective application of alternative sanitization methods (Cavitt & Pathak, 2021).…”
Section: Sanitization Methods For Dry Food Processing Equipment In Lm...mentioning
confidence: 99%
“…Multiple studies have shown that the physicochemical properties of fabrics and surfaces have a pronounced effect on microbial adhesion and proliferation, until reaching irreversible attachment and biofilm formation [7,8]. Surface charge and hydrophobicity level were shown to have an influence on microbial adhesion, with superhydrophobic (water contact angle >150°) having significantly reduced microbial adhesion [9][10][11][12][13]. Hemmatian et al examined the adhesion tendency of Escherichia coli and Staphylococcus aureus on polystyrene and poly lactic acid, both as films and fibers substrates, with modification of wettability by the plasma process using either O2 or C4F8 gas [10].…”
Section: Introductionmentioning
confidence: 99%